Asociación, diámetro - altura en el crecimiento de las plantas de Micrandra spruceana (Baill.) R. E. Schult. en bosque natural y en plantación. Puerto Almendra, Loreto, Perú, 2021 - López Lavajos, Enrique (2022)
The thesis was carried out in a natural forest - Arboretum "El Huayo" and in a plantation of CIEFOR Puerto Almendra - FCF - UNAP, San Juan Bautista district, Maynas province, Loreto region. The objective was to determine the degree of association between diameter and height in the growth of Micrandra spruceana (Baill.) R. E. Schult plants. "shiringa masha" in natural forest and plantation. The variables used for the relationship were diameter and total height of the plants of the species under study. The results indicate that for the diameter-total height relationship of Micrandra spruceana (Baill.) R. E. Schult. "shiringa masha" in natural forest it was observed that the allometric model with the best fit was the cubic; for the plantation it was the power; In addition, in both conditions an excellent degree of relationship was observed between the variables evaluated. Likewise, for the predictions, the equation of the cubic allometric model for the natural forest and the equation of the potential allometric model for the plantation will be applied.